Significance of histologic tumor grade in rectal cancer treated with preoperative chemoradiotherapy followed by curative surgery: A multi-institutional retrospective study. Issue 2 (February 2016) - Song, Jin Ho; Kim, Sung Hwan; Lee, Jong Hoon; Cho, Hyeon Min; Kim, Dae Yong; Kim, Tae Hyun; Kim, Sun Young; Baek, Ji Yeon; Oh, Jae Hwan; Nam, Taek Keun; Yoon, Mee Sun; Jeong, Jae Uk; et al.
Abstract: Background and purpose: To evaluate the pre-treatment clinical factors affecting recurrence and survival in rectal cancer patients who receive preoperative chemoradiotherapy (CRT) and curative surgery. Methods and materials: The clinical data of 1782 patients from 8 institutions in Korea were analyzed. The potential prognostic factors that could be acquired before radical surgery were patient age, gender, clinical T and N stages, tumor size and location, tumor grade, carcinoembryonic antigen (CEA) level, and the concurrent chemotherapy regimen. The relapse-free survival (RFS), overall survival (OS), and cumulative incidence of locoregional and distant recurrence were analyzed according to the clinical factors. Results: Among the pre-treatment clinical factors, tumor grade, pre-CRT CEA level, tumor location, and clinical N stage were significant prognostic factors affecting the RFS. The high-grade tumor was the hazardous factor for RFS on the multivariate analysis [Hazard ratio (HR), 1.83; 95% confidence interval (CI), 1.29–2.58; p  = 0.001]. The 5-year RFS rate for high-grade tumors was significantly lower than that for low-grade tumors (63.8% vs. 78.8%, p  < 0.001). The tumor grade was a significant prognostic factor for distant recurrence (HR, 1.83, 95% CI, 1.29–2.58; p  < 0.001), but not for locoregional recurrence (HR, 1.49, 95% CI, 0.68–3.26; p  = 0.320) on the multivariate analysis. The 5-year OS rate for high-grade tumors was significantly lower than that for low-grade tumors (70.6% vs. 85.5%, p  < 0.001). Conclusion: The tumor grade is the significant pre-treatment clinical factor for recurrence and survival in rectal cancer patients who receive preoperative CRT and curative surgery.